Rehabilitation of Hybrid RC-I Beams with Openings Using CFRP Sheets - Salahaldin, Ali I.; Jomaa’h, Muyasser M.; Oukaili, Nazar A.; Ghaidan, Diyaree J. (Civil Engineering Journal, 2022)
This research presents an experimental investigation of the rehabilitation efficiency of the damaged hybrid reinforced concrete beams with openings in the shear region. The study investigates the difference in retrofitting ability of hybrid beams compared to traditional beams and the effect of two openings compared with one opening equalized to two holes in the area. Five RC beams classified into two groups, A and B, were primarily tested to full-failure under two-point loads. The first group (A) contained beams with normal weight concrete. The second group (hybrid) included beams with lightweight concrete for web and bottom flange, whereas the top flange was made from normal concrete. Two types of openings were considered in this study, rectangular, with dimensions of 100×200 mm, and two square openings with a side dimension of 100 mm. A full wrapping configuration system for the shear region (failure zone) was adopted in this research. Based on the test results, the repaired beams managed to recover their load carrying capacity, stiffness, and structural performance in different degrees. The normal concrete beam regains its total capacity for all types of openings, while the hybrid beams gain 84% of their strength. The strength of hybrid concrete members compared with normal concrete is 81 and 88% for beams of one opening and two openings, respectively. Doi: 10.28991/CEJ-2022-08-01-012 Full Text: PDF